(untitled) (New York, 2000)
Describes six geography themes; each introduces a new concept to help children describe their own adventure as they explore the history, regions and cultures of the United States.
Keywords: Social sciences,Geography,United States,Khoa học xã hội; Study and teaching (Primary),Study and teaching (Primary),Geography,Study and teaching (Primary),Dạy và học